Impact of a Study Abroad Course in Helping Undergraduate Students Affirm Their Career Aspirations to Become Veterinarians: A Qualitative Inquiry - Jose M. Uscanga; M. Craig Edwards; J. Shane Robinson; Rob Terry Jr.; Udaya Desilva (Journal of International Agricultural and Extension Education, 2023)
Twenty-five students who participated in a study abroad course tailored to veterinary medicine during the summer of 2019 were the study’s sources of data. Using photovoice and phenomenology research methods, we sought to explore, understand, and interpret the impact of a study abroad course on pre-vet students’ views regarding veterinary medicine and their aspirations to become veterinarians. Students perceived that veterinary medicine in Mexico was structured differently from the U.S. approach and the nation’s socioeconomic and agroclimatology conditions impacted the delivery of veterinary care and affected the work settings and practice of veterinarians. They not only discerned the uniqueness of veterinary medicine in Mexico, but also recognized its universal components regardless of the culture. The students perceived socio-cultural views about the purpose of animals were significantly different compared to the United States, and veterinary medicine in Mexico was practiced in accord with such. The course contributed to enhancing students’ understanding of veterinary practice options and the professional expectations of a DVM, especially regarding large animal species. In concert with the proposition of human capital theory, the course helped some students confirm their career aspirations and others realize that veterinary medicine was not the best career fit. In some instances, the students’ experiences challenged their preconceived notions of the veterinary profession. Higher Education Institutions should facilitate appropriate and timely learning opportunities for students to understand and confirm their interests in the veterinary profession while undergraduates. Other investigations should also seek to determine factors likely to influence pre-vet students’ career choices.
Keywords: career preparation; global education; Mexico; phenomenology; pre-vet students